On the number of eigenvalues for parameter-dependent diffusion problem on time scales - Gulsen, Tuba; Jadlovska, Irena; Yilmaz, Emrah (Wiley, 2021)
In this study, we consider parameter-dependent diffusion eigenvalue problem on time scales. An upper bound on the number of eigenvalues for this problem on a finite time scale is given.
Keywords: eigenvalue; diffusion equation; time scale